Study of a single receiver system for digital beamforming applications - Tan, ZhaoFeng. (2011)
Digital Beamforming (DBF) technology is an area that is undergoing development due the various advantages and promising features that it may deliver. Conventional DBF technology is however expensive, hence in this final year project (FYP), the author will study the DBF technology application in the context of a single receiver system and realize a hardware test-bed based on a novel low-cost array DBF prototype system proposed by a previous final year project. The proposed system utilizes a microwave signal switch known as a pin diode switch to select echo signals from an N-element phased array. As a result, the number of microwave digital receivers required is reduced from N to one, and this will thus reduce the cost incurred substantially. The design considerations and parameters of the various hardwares involved in the DBF receiver system will also be explored by the author.